Relationship of Sex Hormon Binding Globulin, Thyroid Stimulating Hormone, Testosterone and Prolactine with Body Mass Index (BMI) Value among Iraqi Females in Reproductive Age - Abbas Mehsen Gata1 , Jaleel Samanje2 , Ammer Abd. Mohammed1, Saman Jumaah3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The purpose of this study was to determine the relation between increasing in the body mass index (BMI) value and sex hormones level represented by sex hormon binding globulin (SHBG), Thyroid stimulating hormone (TSH), testosterone and prolactine in 51 women in reproductive age aiming following the life quality of these females. Method: Participants were 51 women from center of Baghdad city. Every female full a questionnaire and sex hormone concentration from each female were measured. Level of FBS and HbA1c test was estimated and designed as exclusion criteria for diabetic mellitus and other metabolic disorders. Body mass index value was compared by demographic properties, Pearson’s correlation coefficient and A stepwise method in linear regression statistic test was applied to detect the association of BMI (kg/m2) with serum sex hormon binding globulin (SHBG), Thyroid stimulating hormone (TSH), testosterone and prolactine and predict the most affected factor. Results: The mean and standard deviation level of most studied parameter were not differences between case study and control females group (obese vs non-obese) in compared with normal value of each test. BMI value were negatively correlated with age and SHBG (nmol/l) level (r = 0.156; P= 0.274) and (r = 0.578; P = 0.00) respectively. While BMI were moderately positive correlated with testosterone (nmol/l), TSH (?IU/ mL) and prolactin (ng/ml) (r = 0.388; P = 0.005), (0.354; P = 0.011) and (0.37; P = 0.006) respectively. Depending on the stepwise method in linear regression analyses, the SHBG (nmol/l) and testosterone (nmol/l) were the most independent predictor factors for BMI in the studied groups (? = 0,484; P = 0.001) and (? = 0.348; P = 0.001) respectively. Conclusions: The most factors affecting obesity identified in the study were SHBG, Testosterone. However, other variables such as age, did not impact the BMI value of participants.